Generalized Ideals of BCK/BCI-Algebras Based on Fuzzy Soft Set Theory - G. Muhiuddin; D. Al-Kadi; K. P. Shum; A. M. Alanazi (Advances in Fuzzy Systems)
In the present paper, using Lukaswize triple-valued logic, we introduce the notion of α,β-intuitionistic fuzzy soft ideal of BCK/BCI-algebras, where α and β are the membership values between an intuitionistic fuzzy soft point and intuitionistic fuzzy set. Moreover, intuitionistic fuzzy soft ideals with thresholds are introduced, and their related properties are investigated.